Modelling possibilities of bolt connections with finite element method - Sarka, Ferenc (Design of Machines and Structures, 2023)
In the article, the possibilities of simulating bolted joints in the Ansys finite ele-ment program are presented. The purpose of the publication is to draw attention to the various simulating options. In the article, different simulation options are used for the same model. The versions to be used are 1) bolt connection without preload 2) bolt-tool, 3) beam-tool, 4) real screw thread modelling. In the article, I rely on previous publications, so some stages are presented in less detail than others. During the simulations, I compare the number of elements used, number of nodes, running time, stress and deformation results. The model used is a closed space loaded with internal pressure, which is divided into two halves. A gasket is installed between the two halves, the two halves are fastened to each other by a row of screws. In order to manage the running times, I only examine the part of the entire model correspond-ing to one screw. The screw joint is loaded with pretension, and the connecting elements with a constant pressure. Where possible in the software, the tightening torque is also taken into account. The results are presented in tabular form for easier comparison.